Optimization of percutaneous biopsy for diagnosis and pretreatment risk assessment of neuroblastoma. Issue 5 (19th February 2020) - Overman, Richard E.; Kartal, Tanvi T.; Cunningham, Aaron J.; Fialkowski, Elizabeth A.; Naik‐Mathuria, Bindi J.; Vasudevan, Sanjeev A.; Malek, Marcus M.; Kalsi, Ranjeet; Le, Hau D.; Stafford, Linda Cherney; Lautz, Timothy B.; Many, Benjamin T.; et al.
Abstract: Background: Image‐guided percutaneous core needle biopsy (PCNB) is increasingly utilized to diagnose solid tumors. The objective of this study is to determine whether PCNB is adequate for modern biologic characterization of neuroblastoma. Procedure: A multi‐institutional retrospective study was performed by the Pediatric Surgical Oncology Research Collaborative on children with neuroblastoma at 12 institutions over a 3‐year period. Data collected included demographics, clinical details, biopsy technique, complications, and adequacy of biopsies for cytogenetic markers utilized by the Children's Oncology Group for risk stratification. Results: A total of 243 children were identified with a diagnosis of neuroblastoma: 79 (32.5%) tumor excision at diagnosis, 94 (38.7%) open incisional biopsy (IB), and 70 (28.8%) PCNB. Compared to IB, there was no significant difference in ability to accurately obtain a primary diagnosis by PCNB (95.7% vs 98.9%, P  = .314) or determine MYCN copy number (92.4% vs 97.8%, P  = .111). The yield for loss of heterozygosity and tumor ploidy was lower with PCNB versus IB (56.1% vs 90.9%, P  < .05; and 58.0% vs. 88.5%, P  < .05). Complications did not differ between groups (2.9 % vs 3.3%, P  = 1.000), though the PCNB group had fewer blood transfusions and lower opioid usage. Efficacy of PCNB was improved for loss of heterozygosity when a pediatric pathologist evaluated the fresh specimen for adequacy. Conclusions: PCNB is a less invasive alternative to open biopsy for primary diagnosis and MYCN oncogene status in patients with neuroblastoma. Our data suggest that PCNB could be optimized for complete genetic analysis by standardized protocols and real‐time pathology assessment of specimen quality.